Isolasi dan Identifikasi Jamur Potensial Pendegradasi Selulosa pada Limbah Pelepah Kelapa Sawit DDaerah Kabupaten Rokan Hulu, Riau - Filza Yulina Ade (Biology Department, Faculty of Science and Technology, Univeristas Jambi, Indonesia, 2016)
In plant there are the cellulose component composition pretty much. Usually there are some microorganisms that can degrade cellulose. A research about isolation and identification of fungus degradation of cellulose on waste palm fronds, had been done using purposive sampling method. This research aimed to look the type of fungus species from waste palm fronds which have the potential to degrade of cellulose and to know can be able in cellulose degradation. Result showed that species of fungus have cellulose degradation potential. Kinds of fungus isolate which founded are Aspergillus niger, Aspergillus oyzae and Rhizopus oryzae. All the fungus isolate have good and big potential in cellulose degradation with afforded to starch degrade at medium to fast rate.